OVERALL QUALITY OF VEGETABLE PRODUCTS UNDER THE INFLUENCE OF VACUUM MICROWAVE DRYING PROCESSES - KOROBKO, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article discusses the importance of consuming fruits and vegetables for reducing the risk of chronic diseases and improving health, which is associated with the presence of biologically active components in them. Since seasonality limits the availability of fresh produce, the task of processing it in order to preserve nutrients, ensure food security and reduce waste is becoming more urgent. Particular attention is paid to drying as the main method of preservation that extends the shelf life of products. The advantages of vacuum freeze-drying (lyophilization) are analyzed, which, due to low temperatures, ensures maximum preservation of biologically active compounds, color, taste and structure of the product. Despite the high quality, commercial limitations of traditional lyophilization encourage the search for innovative solutions. The advantages of vacuum microwave drying are highlighted as a more energy-efficient method, which allows significantly reducing the process time while maintaining the high quality of the dehydrated product. The features of the use of VMS for four types of vegetables are investigated: beets, carrots, onions and cabbage. Their characteristics, influence on the drying process and practical results on preservation of nutritional and organoleptic properties are described in detail. Technological modes of vacuum-freeze drying (freezing temperature, vacuum, microwave power) and their influence on the quality of the final product, including moisture content, waste and raw material consumption, are presented. It is emphasized that the combination of vacuum and microwave heating allows for effective removal of moisture, preserving thermolabile substances and significantly reducing processing time compared to classical lyophilization. The conclusions emphasize the importance of considering both energy efficiency and preservation of biologically active components when developing and optimizing vegetable drying methods.